Fotoliecības par profesora Konstantīna Čakstes piemiņas plāksnes atklāšanu Latvijas Universitātes Mazajā aulā - Rubenis, Rūdolfs (LU Muzejs, 2024)
Par godu Latvijas Centrālās padomes (LCP) Memoranda 80. gadskārtai un LCP priekšsēdētāja, LU profesora un latviešu studentu vienības Austrums biedra Konstantīna Čakstes piemiņas plāksnes atklāšanas 30. gadskārtai, LU Muzejs ir publicējis rakstu par unikālu vēstures avotu - K. Čakstes piemiņas plāksnes atklāšana LU Mazajā aulā 1994. gada 27. septembrī, kad LU svinēja savu 75. jubileju. Rakstā tiek skaidrota K. Čakstes piemiņas kopšanas tradīcijas uzsākšanas norise, tās nozīme LU un Latvijas valsts vēsturē. Šī tēma ir aktuāla saistībā ar LU 105. jubileju, kas tiks svinēta vienlaikus ar K. Čakstes piemiņas plāksnes atklāšanas 30. gadskārtas pieminēšanu.

On the occasion of the 80th anniversary of the Memorandum of the Latvian Central Council (LCP) and the 30th anniversary of the unveiling of the memorial plaque to Konstantinas Čakste, the LCP chairman, professor of the University of Latvia and member of the Latvian student union "Austrums", the Museum of the University of Latvia has published an article about a unique historical source - the unveiling of the K. Čakste memorial plaque in the Aula Minor of the University of Latvia on 27th September 1994, when the University of Latvia celebrated its 75th anniversary. The article explains the beginning of the tradition of K. Čakste commemoration, its significance in the history of the University of Latvia and the Latvian state. This topic is topical in the context of the 105th anniversary of the University of Latvia, which will be celebrated at the same time as the 30th anniversary of the unveiling of the K. Čakste memorial plaque.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Latvijas Centrālā padome; Latvijas Universitāte; Latvijas valsts nepārtrauktība; Studentu akadēmiskās mūža organizācijas; Nacionālā piemiņa; Nacionālā pretošanās; Otrais pasaules karš (1939-1945); Latvijas Universitātes mācībspēki; Latvian Central council; The University of Latvia; Continuity of the Latvian state; Student academical lifetime organisations; National rememberence; National resistance; Second World war (1939-1945); Teaching staff of the University of Latvia